Poglądy na cele kary w Rzeczypospolitej czasów stanisławowskich - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Another one in a series of publications on the history of criminal law thought in the eighteenth century Republic of Poland covered the views on the purposes of criminal sanctions which had been presented in Stanisław’s Poland. It presents the opinions, arguments, requests and suggestions which, in connection with this subject, appeared in the said period in journalism, legal literature, as well as private correspondence, of both the greatest Polish jurists of the era, as well as anonymous opinions, being an emanation of views of the then „political nation,” ie the representatives of Polish and Lithuanian gentry.Confronting the views of thinkers and legal practitioners of the Polish Enlightenment with the ideas of most prominent representatives of the eighteenth-century Western thought, the author conducts inquiries about the similarities and differences between the views of philosophers, lawyers and politicians, while trying to pay attention to the relationship between the force of traditionalist argument and expansion of innovative ideas, sometimes almost revolutionary.
Keywords: historia; historia prawa; prawo karne; kara; prawo polskie; Oświecenie